Modeling and Practical Implementation of Separately Excited DC Motor Water Pump System - Karim, Rawaz Hama Aziz H.; Abdulrahman, Alaa (Sulaimani Journal for Engineering Sciences, 2023)
The requirement of using DC motor for driven water pump has gained more attention in the irrigation system due to high performance and wide range of speed control of DC motor and difficult improvement in physical behavior of water pump system. This paper studies on modeling and practical implementation of a separately excited DC motor (SEDCM) driven water pump system. The pump capacity and charge flow has been increased by manipulating shaft speed of the SEDCM using field weakening control. The mathematical model is derived for electro mechanical equations of motor as well as the pump equations. Three different tests have been carried out to prove the simulated model performances and validate the system response. For each particular test, the speed and armature current of the motor has been measured as well as the flow rate at constant pump head. Performance of the model has been compared with the practical implementation and they’re matched well.
Keywords: separately excited DC motor (SEDCM); water pump; field weakening